Artificial Intelligence and African Studies. - Emeagwali, Gloria (Comparative Civilizations Review)
African Studies is a conglomerate of multidisciplinary academic fields that include paleontology, history, literature, linguistics, philosophy, African Traditional Religion and theology, art, and Afrofuturism, as well as African Indigenous Knowledge Systems. This paper focuses on the latter, namely African Indigenous Knowledge Systems (AIKS), and African Studies, in general, from the viewpoint of two chatbots, namely, ChatGPT-4, and DeepSeek v.3. Do these models make a break with Eurocentrism and prevent unbiased information on AIKS? Are the underlying conceptual issues underpinning AIKS fully grasped, and if so, what are some relevant examples of this accomplishment? How do these programs respond to specialized aspects of AIKS such as Indigenous African Mathematics? These are among the issues explored in this paper.